The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jseint.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

The modern reverse shoulder arthroplasty and an updated systematic review for each complication: part II

Abstract: Background Globally, reverse shoulder arthroplasty (RSA) has moved away from the Grammont design to modern prosthesis designs. The purpose of this study was to provide a focused, updated systematic review for each of the most common complications of RSA by limiting each search to publications after 2010. In this part II, the following were examined: (1) instability, (2) humerus/glenoid fracture, (3) acromial/scapular spine fractures (AF/SSF), and (4) problems/miscellaneous. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 288 publications
1
29
0
2
Order By: Relevance
“…A recent systematic review which included 14,235 RTSAs reported a rate of 2.6%. 11 Others have reported higher rates, of up to 10%. 26 An intact acromion as the origin of the deltoid muscle is crucial to the function of a RTSA.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent systematic review which included 14,235 RTSAs reported a rate of 2.6%. 11 Others have reported higher rates, of up to 10%. 26 An intact acromion as the origin of the deltoid muscle is crucial to the function of a RTSA.…”
Section: Discussionmentioning
confidence: 96%
“…8,9 The most common complications are instability, periprosthetic infection, aseptic glenoid loosening, and fractures of the body or spine of the acromion. [8][9][10][11] Various review articles have dealt with each complication separately. [9][10][11][12][13][14] However, few have reported the overall complication rate and clinical outcome in a large cohort of patients with sufficient follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auch eine codierte Demenzerkrankung zum Zeitpunkt der Operation ist mit einer mittleren Kostensteigerung von β = 682,12 EUR (95 %-KI: 477,28-886,95 EUR; p < 0,001) assoziiert. [26,27]. Die hohe Zufriedenheit der behandelnden Unfallchirurgen deckt sich auch mit den Ergebnissen der Delphi-Studie, welche in einem randomisiertkontrollierten Multicenterstudiendesign eine bessere Schulterfunktionalität gemessen am Constant Score nach inverser Schulterprothese im direkten Vergleich zur winkelstabilen Plattenosteosynthese nach AO(Arbeitsgemeinschaft für Osteosynthesefragen)-Typ-B2-und -C2-Frakturen in einem 2-Jahres-Follow-up nachweisen konnte [6].…”
Section: Einfluss Der Komorbiditäten Auf Kosten Und Liegedauerunclassified
“…The treatment of rotator cuff tears was revolutionized with the introduction of RSA, which provides significant improvements in functional and clinical outcomes for many different shoulder pathologies [1]. Studies reporting on long-term outcomes of Grammontstyle designs have reported consistent limited restoration of external rotation [2].…”
Section: Introductionmentioning
confidence: 99%